Eosinophilic fasciitis with subjacent myositis. Issue 3 (27th March 2017) - Whitlock, Julia B.; Dimberg, Elliot L.; Selcen, Duygu; Rubin, Devon I.
ABSTRACT: Introduction: Eosinophilic fasciitis (EF) is a rare disorder that can present with muscle symptoms that mimic other neuromuscular diseases. Methods: We report the case of a 43‐year‐old woman with chronic muscle aches, tightness, and stiffness with hypertrophied, well‐defined muscles despite physical inactivity, and thickened skin with reduced elasticity and discoloration. Results: Except for mild peripheral eosinophilia, laboratory studies, including blood count, electrolytes, paraneoplastic panel, muscle enzymes, thyroid function, and serum protein electrophoresis, were normal. Nerve conduction studies and needle electromyography were normal. Magnetic resonance imaging of the thighs demonstrated superficial and deep fascial thickening with T2 hyperintensity and post‐gadolinium enhancement. Fascial and muscle biopsy demonstrated an inflammatory exudate in the perimysium and endomysium with fragmented perimysial connective tissue and thickened, inflamed fascia. EF was diagnosed. The patient was treated with methotrexate and prednisone followed by improvement of muscle stiffness and tightness. Conclusion: EF should be considered when patients present with muscle pain or enlarged muscles. Muscle Nerve 56 : 525–529, 2017